Benign mesocolon schwannoma in PET/CT and immunohistochemistry assessement: a case report - Kula, Zbigniew; Jóźwicki, Wojciech; Zegarski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2012)
Schwannoma is a common soft tissue tumour, but it appears to be very rare in the gastrointestinal tract. Benign schwannoma develops extremely rarely in the mesocolon, with only 2 patients reported in the literature. A 75-year-old woman was admitted to our Department of Oncological Surgery with an abdominal mass, which was discovered incidentally during abdominal ultrasound examination. Positron emission tomography/ computed tomography imaging with the use of 18F-fluorodeoxyglucose (FDG PET/CT) showed an abnormal mass in the upper right abdomen with the presence of diffuse FDG uptake. A laparotomy revealed an encapsulated, non-invasive mesocolon tumour in the hepatic flexure region. Definitive diagnosis was confirmed by the histopathological examination of the postoperative preparation. Immunohistochemical staining confirmed benign mesocolon schwannoma. Previous cases indicate that schwannomas in the mesocolon are benign tumours. Our patient had a good prognosis even after enucleation treatment. Although schwannomas are very rare and generally asymptomatic, the differential diagnosis of schwannomas and gastrointestinal stromal tumours is important for practical purposes.